2014
DOI: 10.3174/ajnr.a3825
|View full text |Cite
|
Sign up to set email alerts
|

Glioma: Application of Histogram Analysis of Pharmacokinetic Parameters from T1-Weighted Dynamic Contrast-Enhanced MR Imaging to Tumor Grading

Abstract: BACKGROUND AND PURPOSE:The usefulness of pharmacokinetic parameters for glioma grading has been reported based on the perfusion data from parts of entire-tumor volumes. However, the perfusion values may not reflect the entire-tumor characteristics. Our aim was to investigate the feasibility of glioma grading by using histogram analyses of pharmacokinetic parameters including the volume transfer constant, extravascular extracellular space volume per unit volume of tissue, and blood plasma volume per unit volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 27 publications
5
62
1
Order By: Relevance
“…The diagnostic accuracies of DCE-derived parameters in this study were in the range of previously published data from 2 studies, 1 by using a hot spot method and 1 by using histogram analysis. 13,18 The accuracy of DSC-derived rCBV in this study was also similar to that in previous studies using hot spot analysis. 1,19 Using the bookend T1 mapping and phase-derived VIF, we also found that DCE-derived Vp and K trans were lower for grade II than for grade III astrocytomas.…”
Section: Discussionsupporting
confidence: 75%
“…The diagnostic accuracies of DCE-derived parameters in this study were in the range of previously published data from 2 studies, 1 by using a hot spot method and 1 by using histogram analysis. 13,18 The accuracy of DSC-derived rCBV in this study was also similar to that in previous studies using hot spot analysis. 1,19 Using the bookend T1 mapping and phase-derived VIF, we also found that DCE-derived Vp and K trans were lower for grade II than for grade III astrocytomas.…”
Section: Discussionsupporting
confidence: 75%
“…12 Advanced MRI techniques have shown potentials in evaluating the key pathological features of the glioma and can potentially help tumor grading. [13][14][15][16][17][18] For example, parameters derived from diffusion weighted imaging and diffusion kurtosis imaging contributed to discrimination between high-grade and low-grade gliomas. 19 Furthermore, histological grading is more and more refined by genetic characteristics of astrocytomas, which has been partially incorporated in the latest tumor classifications.…”
Section: Discussionmentioning
confidence: 99%
“…T1 mapping provides a method to calculate the T1 value of each voxel during the non-contrast phase and has been shown not to significantly alter DCE quantification. 18,19 Hence, we do not perform T1 mapping for DCE correction at our institution, and it was not available for image processing in this study.…”
Section: Methodsmentioning
confidence: 99%